2008
DOI: 10.1063/1.2967194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal electrodes on the resistive memory switching property of NiO thin films

Abstract: The effects of various metal electrodes on the resistive switching of NiO thin films were investigated. Contrary to the belief that Pt is used for its high work function, which enables Ohmic contact to p-type NiO, resistive switching was observed in films with Ta or Al electrodes with a low work function in the as-deposited state. The resistive switching of films with a Ag or Cu top electrode with a low work function and high free energy of oxidation shows the importance of the formation of an oxide layer at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
136
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 11 publications
1
136
1
1
Order By: Relevance
“…[128] Melanin is used in cosmetic products, sometimes in combination with photoactive oxides. Melanin (both synthetic and natural)-TiO 2 interactions have been investigated, [129][130][131] in particular the photocatalytic activity of TiO 2 on the process of DHICA polymerization (Fig. 7).…”
Section: Melanin/metal Oxides Interfaces: Adhesion Biocompatibilitymentioning
confidence: 99%
“…[128] Melanin is used in cosmetic products, sometimes in combination with photoactive oxides. Melanin (both synthetic and natural)-TiO 2 interactions have been investigated, [129][130][131] in particular the photocatalytic activity of TiO 2 on the process of DHICA polymerization (Fig. 7).…”
Section: Melanin/metal Oxides Interfaces: Adhesion Biocompatibilitymentioning
confidence: 99%
“…18)- 19) Their results showed that different from the belief that due to its high work function, Pt enables Ohmic contact to p-type NiO, resistive switching was observed in NiO thin films using Ta or Al electrodes with a low work function. The resistive switching of films using an Ag or Cu top electrode with a low work function and high free energy of oxidation shows the importance of the formation of an oxide layer at the metal/NiO interface.…”
Section: Nio Thin Filmsmentioning
confidence: 38%
“…The dependence of resistive switching on both top and bottom electrode materials has recently been reported [4,15,37]. For some RRAM devices, different electrode materials seem to cause different resistive-switching behaviors, which might depend on the barrier height at the electrode/resistive switching-layer interface.…”
Section: Electrode Materialsmentioning
confidence: 99%